2017
DOI: 10.1152/physiol.00031.2016
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Metabolism in Endothelial Cell Function and Vascular Disease

Abstract: The importance of endothelial cell (EC) metabolism and its regulatory role in the angiogenic behavior of ECs during vessel formation and in the function of different EC subtypes determined by different vascular beds has been recognized only in the last few years. Even more importantly, apart from a role of nitric oxide and reactive oxygen species in EC dysfunction, deregulations of EC metabolism in disease only recently received increasing attention. Although comprehensive metabolic characterization of ECs sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 173 publications
(202 reference statements)
0
51
0
3
Order By: Relevance
“…Although EC function has been demonstrated to be regulated downstream of metabolic reprogramming (Bierhansl, Conradi et al 2017), metabolic activity of senescent EC is not particularly well described. Concomitant with a decrease in parameters of EC function assessed either ex vivo (Figure 3) or in primary cells isolated following in vivo exposure (Figure 5), we see a dramatic decrease in metabolic activity in hUVEC exposed to 3 µg/mL epirubicin (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EC function has been demonstrated to be regulated downstream of metabolic reprogramming (Bierhansl, Conradi et al 2017), metabolic activity of senescent EC is not particularly well described. Concomitant with a decrease in parameters of EC function assessed either ex vivo (Figure 3) or in primary cells isolated following in vivo exposure (Figure 5), we see a dramatic decrease in metabolic activity in hUVEC exposed to 3 µg/mL epirubicin (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that endothelial metabolism governs, to a significant extent, endothelial function (Bierhansl, Conradi et al 2017). To evaluate metabolic activity in hUVEC exposed to epirubicin, cells were subjected to mitochondrial stress tests (Figure 4A, B) and glucose stress tests (Figure 4C, D).…”
Section: Metabolic Activity Is Compromised In Huvec Exposed To Epirubmentioning
confidence: 99%
“…(3) Next, the quiescent "phalanx cells" mature neovessels featured by a typical cobblestone shape. (4) Finally, in order to form a tighter vessel for proper stability and barrier function, pericytes secrete platelet-derived growth factor-B (PDGF-B) and subsequently recruit VSMC expressing PDGF receptor β [79,80]. Recently, the roles of metabolism remodeling of endothelial cells in angiogenesis are attached by many researchers.…”
Section: The Mechanism Of Revascularizationmentioning
confidence: 99%
“…monoclonal antibodies such as Avastin or receptor tyrosine kinase inhibitors like Sunitinib, are used to target colorectal, non-small-cell lung, ovarian, peritoneal, renal cell and cervical cancers; unfortunately, in most cases treatment provides only a modest improvement in overall patient survival (33). However, reprogramming EC metabolism in the tumour environment may also modulate the excessive angiogenesis (34), as the tumour environment is deprived of nutrients and oxygen, and both tumour and stromal cells must produce large amounts of energy and macromolecular precursors (nucleotides, lipids, amino acids) for rapid growth. EC metabolism and its regulation are therefore centrally involved in vessel growth, survival and function, and may offer novel and alternative targets to interfere with or stimulate angiogenesis.…”
Section: Tumoursmentioning
confidence: 99%